2020
DOI: 10.21203/rs.2.21536/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical learning environment of nursing and midwifery students in Ghana

Abstract: Background Data on student experience of the clinical learning environment in Ghana are scarce. We therefore aimed to assess students’ evaluation of the clinical learning environment and the factors that influence their learning experience.Methods This was a cross-sectional survey of 225 undergraduate nursing and midwifery students. We used the Clinical Learning Environment and Supervision + Nurse Teacher (CLES +T) evaluation scale to assess students’ experience of their clinical placement. The association bet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
4
1
1
Order By: Relevance
“…e reason behind this may be due that their satisfaction increased as students progressed through the program that the higher-year students expressed higher confidence in clinical knowledge and skills. On the contrary, a study conducted in Ghana found that the mean CLES + T score was not associated with the year of study even though third-year students had higher scores than fourth-year students [1]. Our findings highlight that the satisfaction with a CLE of nursing students is associated with the type of hospital in which their last clinical placement was held.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…e reason behind this may be due that their satisfaction increased as students progressed through the program that the higher-year students expressed higher confidence in clinical knowledge and skills. On the contrary, a study conducted in Ghana found that the mean CLES + T score was not associated with the year of study even though third-year students had higher scores than fourth-year students [1]. Our findings highlight that the satisfaction with a CLE of nursing students is associated with the type of hospital in which their last clinical placement was held.…”
Section: Discussioncontrasting
confidence: 84%
“…Contrary to this, the most satisfactory area for student nurses was the leadership style (1.44) of their mentors in their clinical learning environment, and they were least satisfied with the student-nurse relationship (1.41) and content context balance (1.41) in their clinical learning environment [27]. Furthermore, a study conducted in Ghana demonstrated that the most satisfactory area for student nurses was the leadership style of the ward manager (3.63) [1]. e differences in mean scores in dimensions of the CLES + T were found in different studies that we reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations